Microbiological contamination and associated factors in breast milk from the human milk bank of a Hospital in Peru - Rosales-Rimache, Jaime (2021)
Objetive: Estimate microbiological contamination and identify its associated factors in breast milk within the BLH of a Hospital in Peru. The study. Cross-sectional design, where a physical, chemical and microbiological evaluation was carried out on samples of breast milk. Findings. We evaluated 187 milk samples donated by mothers. The average Dornic acidity and crematocrit were 5.2 ± 1.6 and 2.7 ± 0.9%, and the microbiological contamination represented 3.7% of the total samples evaluated, isolating Acynetobacter iwoffi, Moraxela lacunata, Pseudomona aeruginosa and Staphylococcus negative coagulase. It was evidenced that the pH of the milk was the only variable associated with microbiological contamination (OR: 3.7 IC95: 1.5-8.8). Conclusion. The increase in pH is a factor associated with microbiological contamination in donated milk samples at the BLH of a Hospital in Peru, so it is advisable to re-evaluate the acceptability criteria of the pH range of donated breast milk.